Avaliação das condições de extração para posterior especiação de arsênio em alimentos por LC-ICP-MS - Seeger, Tássia da Silva (2019)
Arsenic is a toxic element with carcinogenic and mutagenic characteristics. However, its toxicity is associated with their species, because some present different toxicities. In this sense, speciation analysis is mandatory for understanding the availability of As and its effects in different organisms. The most common As species are inorganic [such as As(III) and As(V)] and organic [methylated derivatives, e.g. dimethylarsenic (DMA) and monomethylarsenic (MMA)]. Since speciation analysis requires that the species be preserved throughout the procedures involved in the analytical sequence, from the sample preparation up to the detection, several aspects should be carefully investigated to assure the species preservation. Sample preparation is one of the most critical steps during analysis, mainly taking into account the factors that may influence the species stability. In general, extraction methods are used for speciation analysis, since they show milder conditions regarding to the temperature and reagents concentration. These extraction procedures can be performed by conventional extraction (conductive heating and mechanical stirring), microwaveassisted extraction (MAE), ultrasonic-assisted extraction (UAE), among others. Although conventional extraction and MAE present widespread use, the application of ultrasound have not been well studied for As speciation analysis, which generates a gap in the literature about the effects of this type of energy on As species. In this work, a critical study was carried out evaluating the main factors that could influence the species stability and extraction efficiency. Considering the variety of As species in different types of matrices, samples of algae, rice and fish were chosen for this study, covering a high as possible number of As species. Some parameters such as type and concentration of extraction solution, time and temperature of extraction were evaluated for the extraction efficiency, while the concentration of the extraction solution and the addition of ions was used to evaluate the stability of As species. It was observed that the energy source used in the extraction method did not influence the stability of the species, as well the extraction efficiency. On the other hand, it was observed that the temperature and extraction time influenced the extraction efficiency, whereas the concentration of HNO3 as extraction solution, influenced the extraction efficiency, resulting in the conversion of the unknown As species (named UK1) present in the algae. After ions addition before extraction, it was observed that the addition of Fe3+ in algae provides the conversion of UK1 species into As(III) and As(V) and in rice provides the conversion of As(III) and DMA into As(V). In addition, the quantification of As species in the samples was performed using the optimized extraction conditions for each matrix without species conversion. The limit of quantification of the method was 0.06 μg g-1..